Amyand’s Hernia Complicated by Omental Infarct Presenting as Acute Scrotum: Report of a Case and Review of the Literature - Reza Khorramirouz; Amin Bagheri; Alireza Aalam Sahebpour; Abdol-Mohammad Kajbafzadeh (Case Reports in Surgery)
Inguinal hernia with acute appendicitis known as Amyand’s hernia is uncommon. It may clinically manifest as acute scrotum, inguinal lymphadenitis, or strangulated hernia. The presentation of Amyand’s hernia with acute scrotum has been rarely described. Also, the manifestation of infarcted omentum in the inguinal hernia has been described in one case previously. However, the coexistence of perforated appendix with infarcted omentum in the hernia sac which manifests acute scrotum has not been described previously. Herein, we described a case of a 5-year-old boy, admitted with right tense, painful, and erythematous scrotum in the emergency room. The diagnosis of herniated appendicitis was performed preoperatively by ultrasound. Moreover, the ischemic omentum was confirmed during surgery.